Effect of Local Original Revenue and Economic Growth to Human Development Index of Regencies/Cities in Bali Province - Anak Agung Gde Mantra Suarjana; Ni Gusti Nyoman Sucimurni (Soshum: Jurnal Sosial dan Humaniora, 2018)
The objectives of this study are: (1) To analyze Local Original Revenue (PAD) on the Human Development Index in District / City Governments in Bali Province. (2) To analyze the economic influence of the Human Development Index in District / City Governments in Bali Province. (3) To analyze the effect of Original Local Revenue (PAD) and Economic Growth simultaneously on the Human Development Index in District / City Governments in Bali Province. (4) To analyze the pattern of the relationship between Economic Growth and the Human Development Index in each Regency / City in Bali Province. The purposive sampling technique used is in accordance with the objectives of the researcher with several considerations. Data collection is done with the documentation techniques. The analysis technique used is the multiple regression techniques. The results of data analysis show that the Local Original Revenue (PAD) is positive and significant towards the Human Development Index (HDI) in the District / City Governments in Bali Province. Economic Growth has a positive and significant effect on the Human Development Index (HDI) in District / City Governments in Bali Province. (3) Local Original Revenue (PAD) and Economic Growth simultaneously positive and significant to the Human Development Index (HDI) in the District / City Government in Bali Province. The pattern of the relationship between Economic Growth (HDI) in each Regency / City in the Province of Bali shows that Badung, Gianyar and Denpasar City are included in the Fast and Fast Growing Regions category. Buleleng Regency belongs to the category of Fast Developing Regions. Tabanan Regency is in the category of Advanced Regions Not Yet Depressed. Jembrana, Klungkung, Bangli, and Karangasem Regencies include the category of Disadvantaged Areas.